North Kolaka District Sanitation Strategy - Anhar, Eddy; Kadir, Ishak; Sugiyarto Soeparyanto, Try; Nasruddin, Nasruddin; Sahrul, Sahrul (Departement of Civil Engineering, Universitas Winaya Mukti, 2025)
North Kolaka Regency has prepared a District Sanitation Strategy (SSK) document in 2014 as a guideline for sector sanitation development during the 2015-2019 period. With the end of this period, updating the SSK in 2021 is very important for planning sanitation development for the next five years in accordance with actual conditions and new challenges. This document aims to increase coverage of safe and adequate sanitation services through planning that is integrated with regional, provincial and national policies. The update was carried out by the Housing and Settlement Areas Working Group (Pokja PKP) with a participatory approach. The methods used include evaluating existing conditions, analyzing images, as well as establishing a vision, mission and strategy for sanitation development. It is hoped that the results of this update will encourage cross-sector collaboration and involve the role of the private sector and the community, so as to optimize the management of domestic wastewater, solid waste and drainage. The results of the analysis show that achieving sanitation access in North Kolaka still requires significant improvement to achieve the 2020-2024 RPJMN target, including reducing the practice of open defecation (defecation). The strategy formulated includes strengthening institutions, optimizing faecal sludge processing infrastructure, and outreach to the community to strengthen awareness and participation.